New Insights into the Formation Mechanism of Intertwining Interfaces in Cold Spray - Lupoi, Rocco; Yin, Shuo (ASM International, 2018)
﻿﻿Experimental investigation supported by numerical modeling was conducted to explore the formation mechanism of intertwining interface in cold spray. The result revealed that low particle impact velocity and the consequent low deposition efficiency were the essential reason for inducing intertwining interface. In addition, intertwining interface was found to generate at very beginning of coating deposition; further particle deposition posed negligible effect on the formation of intertwining interface. Based on the experimental and numerical analysis, for the first time, the formation mechanism of intertwining interface was concluded and proposed in this paper. Low deposition efficiency led to slow coating growing rate. Therefore, at the beginning of the coating deposition, a large number of rebound particles repetitively hit the very thin single-layer or double-layer coating, forming a shot-peening effect. Such effect resulted in periodic shear stress and plastic strain in the first-layer coating. Particles of the first-layer coating were elongated and fractured and mixed with the substrate material to form the intertwining structure.
ITSC 2018Proceedings of the International Thermal Spray Conference
PUBLISHED
Orlando (US)
Keywords: Cold spray; Coatings